Financial Performance of Tourism Businesses in Labuan Bajo Tourist Area, Indonesia - YUDHOYONO, Edhie Baskoro; SIREGAR, Hermanto; ACHSANI, Noer Azam; IRAWAN, Tony (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.12.2(50).13, 2021)
Labuan Bajo is one of the tourism destinations that are prioritized in Indonesia's national development. However, the contribution of tourism in Labuan Bajo to the economy and welfare of the surrounding community is still less than optimal even though there have been many attempts to stand around the tourist area of Labuan Bajo. This study aimed to analyse the financial performance of tourism businesses in the tourist area of Labuan Bajo, which is one of the tourism destinations prioritized by the Indonesian government. Data was collected through a questionnaire distributed to 221 respondents of tourism business actors in the tourist area of Labuan Bajo. The results of this study revealed that tourism business actors in Labuan Bajo were quite diverse in terms of tourism business permits, business scale, and business entities. Also, the growth of tourism businesses in the tourist area of Labuan Bajo was quite significant in 2017-2018. The results of the financial performance analysis showed that the income was relatively high in tourism businesses that have been operating for a long time. They were funded by bank loans, had large capital, adopted information technology, and members of certain tourism organizations. In general, the financial performance of the tourism business in Labuan Bajo has not been optimal, particularly in managing assets for profit.